Exploring occupational services rendered at public high schools for teachers in Vhembe district, Limpopo - Legege, Fhatuwani Joseph (My University, 2016)
Due to the lack of direct access to Human Resource (HR) offices, most public schools are usually neglected with regards to issues of health and occupational services. Teachers are faced with occupational challenges, such as stress, physical and mental health issues, increased work load, long working hours, unrealistic deadlines, inadequate remuneration, HIV/AIDS, poor personal financial management and relationship problems. Therefore, this requires teachers to have access to professional occupational services which aim to support and enhance their wellbeing when required. The research study explored on occupational services rendered at rural public high schools for teachers in Limpopo. The qualitative research approach and a case study research design were utilised. A type of non-probability sampling, purposive sampling also known as a judgemental sampling was used to select the research participants. The sample consisted of 19 teachers from two public high schools, who participated in three focus groups. With the various findings from the study and identifying challenges in the various schools, it is evident that the Department of Education, Limpopo needs to prioritise the provision of occupational health services to teachers in the rural areas. Such services are anticipated to enhance the wellbeing of teachers, which is further hoped, that learners will benefit from quality education as provided by teachers, impacting positively on the year end outcomes.
A report on a research study presented to The Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand In partial fulfilment of the requirements for the degree Master of Arts in Occupational Social Work March, 2016
Keywords: High school teachers--Job stress--South Africa; High school teachers--Work load--South Africa; High school teachers--Mental health--South Africa; High school teachers--South Africa--Psychology